Gas in the Kidneys? Emphysematous Pyelonephritis: A Case Series. (October 2014) - Ashley, Elizabeth; Chee, Nigel; Hickson, Guy; Williams, Matthew
We examine three cases of emphysematous pyelonephritis that presented to our intensive care unit over a three-year period. The three patients were all female, had co-existing diabetes mellitus, and developed acute kidney injury (AKI), hyponatraemia and thrombocytopenia during the course of their illness. All three were managed by radiological intervention along with medical management. Two of the three patients also had surgical management (nephrectomy), which was carried out at different stages of the acute illness. All three patients survived to hospital discharge. There was an inconsistent approach to the management of this rare condition, both in our cases and in similar cases reported in the medical literature. These cases underline the importance of maintaining open dialogue between the intensive care and the specialist teams to aid the decision-making required in these patients, who have a potentially high mortality.